'Burglar alarms' and the making of social risks: 'Tourism capacity' and its controversies in Hong Kong. Issue 1 (2nd May 2017) - Chan, Chi Kit
Abstract : Purpose: This paper explicates news making process of social risks in the midst of inconclusive social facts and contested interpretation of social consequences. Specifically, the author aims to investigate how journalists perform the normative role of "Burglar Alarms" – raising social concern to risks and problems amid uncertainties stemming from risk society. Shedding light on the controversies of "tourism capacity" in Hong Kong, this study unravels how news discourses represented the social risks of "outnumbered" Chinese tourists amid ambiguous facts and questionable credibility of news sources. Content analysis of news discourses and interviews with journalists showed that there are emerging journalistic practices – namely, witnessing performativity and opinionated objectivity – to construct social risks in view of less credible news sources, volatile public opinion and highly speculative news events. Design/methodology/approach: Content analysis of news discourses was represented in the press and in-depth interviews with journalists. Findings: Content analysis of news discourses and interviews with journalists showed that there are emerging journalistic practices – namely, witnessing performativity and opinionated objectivity – to construct social risks in view of less credible news sources, volatile public opinion and highly speculative news events. Originality/value: Informed by the theory of risk society, this paper explores how journalists set out the "Burglar Alarms" of social risks by constructing social facts in the midst of questionable authorities and limited expert advice. Instead of relying on authoritative interpretation of social risks, journalists performed as the witnesses to the "reality" of social risks and problems, however selective and interpretative, to the audience. They also articulated to the general will of the people and selective representation of everyday life experience so as to justify their opinionated news angle and the pledge to news objectivity.